English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2007-01-18 10:23:39 · 10 answers · asked by Kate 1 in Science & Mathematics Mathematics

10 answers

6x-7=3x-5
3x=2
x=2/3

2007-01-18 10:26:05 · answer #1 · answered by A 150 Days Of Flood 4 · 1 3

Presumably,
6x - 7 + 3x = 5
Add 7 to both sides
6x + 7 - 7 + 3x = 5 + 7
6x + 3x = 12
Combine the x coefficients
9x = 12
divide both sides by 9
(9/9)x = 12/9
simplify
x = 4/3

edit:
yeah, the other looks more like what you would get as an exercise.
6x - 7 = 3x + 5

The others have shown you how to solve this one.

2007-01-18 10:33:35 · answer #2 · answered by Helmut 7 · 0 0

I'm assuming you mean: 6x -7 = 3x + 5
Isolate x by moving all terms with x's to the left hand side:
6x - 3x - 7 = 3x - 3x + 5
3x - 7 = 5
Move all terms without x's to the right hand side:
3x - 7 + 7 = 5 + 7
3x = 12
Divide by 3 to get x (or rather, 1x):
3x/3 = 12/3
1x = 4
x = 4

=)

2007-01-18 10:27:24 · answer #3 · answered by Jess 2 · 1 0

Why do you have 6x-7 = 3x = 5? Did you mean to type >>>
6x-7=3x-5 Or, 6x-7=3x+5? I'll solve the problem with "3x - 5" and "3x+5" :-)

1. 6x - 7 = 3x - 5
First: combine "like" terms > add 7 to both sides (when you move a variable/term to the opposite side-use the opposite sign)...

6x - 7 + 7 = 3x - 5 + 7
6x = 3x + 2

Sec: subtract "3x" from both sides...

6x - 3x = 2
3x = 2

Third: solve for "x" by isolating it on one side > divide both sides by 3...

3x/3 = 2/3
x = 2/3


2. 6x - 7 = 3x + 5
First: add "7" to both sides...

6x - 7 + 7 = 3x + 5 +7
6x = 3x + 12

Sec: subtract "3x" from both sides...

6x - 3x = 3x - 3x + 12
3x = 12

Third: divide both sides by - 2...

3x/3 = 12/3
x = 4

2007-01-18 10:59:59 · answer #4 · answered by ♪♥Annie♥♪ 6 · 0 0

5x+7=3x-5 pass the (x)'s to a minimum of one element and the nums to the different(subtract (3x) and (7) from the two facets 5x -3x +7-7 =3x-3x -5 -7 2x = -12 divide the two facets by using 2 to isolate (x) 2x/2 = -12/2 x = -6

2016-10-31 11:30:21 · answer #5 · answered by ? 4 · 0 0

move the 3x to the left and then subtract it which is 3x-7=5.
then move the -7 to the right and it will be 3x=2
then divide 3 on both sides
x=2/3

2007-01-18 10:32:02 · answer #6 · answered by Anna 1 · 1 1

I'm assuming that "second" equals sign is a typo, and should be a + sign.

6x -7 = 3x + 5
6x - 3x = 5+7
3x = 12
x = 12/3
x = 4

2007-01-18 10:26:56 · answer #7 · answered by Wolfshadow 3 · 1 0

6x-7=3x=5? That's too many equal signs!
If the first is a subtraction sign, simplify using the addition/subtraction property of equality.
6x-7-3x=5
3x=12
x=4
If the first is an addition sign, simplify using the addition/subtraction property of equality.
6x-7+3x=5
9x=12
x=4/3
If the second is a subtraction sign, simplify using the addition/subtraction property of equality.
6x-7=3x-5
3x=2
x=2/3
If the second is an addition sign, simplify using the addition/subtraction property of equality.
6x-7=3x+5
3x=12
x=4

2007-01-18 10:31:59 · answer #8 · answered by JAB 2 · 1 0

6x-7=3x+5
3x=12
x=4

2007-01-18 10:29:11 · answer #9 · answered by      7 · 1 0

I must be dumber than you are, I don't have a clue what it means.

2007-01-18 10:27:19 · answer #10 · answered by Anonymous · 0 3

fedest.com, questions and answers